Prediction model of all-cause death based on balance ability among middle-aged and older Chinese adults of overweight and obesity - Xie, Kaihong; Han, Xiao; Lu, Jia; Xu, Xiao; Hu, Xuanhan (Frontiers in Public Health, 2022)
Background Advances in studies using body indicators to predict death risk. Estimating the balance ability of death risk in middle-aged and older Chinese with overweight and obesity is still challenging. Methods A retrospective analysis of the data from the China Health and Retirement Study from January 2011 to December 2018. A total of 8,632 participants were randomly divided into 7:3 a training group and a verification group, respectively. Univariable Cox analysis was used to prescreen 17 potential predictors for incorporation in the subsequent multivariable Cox analysis. 9 variables were included in the nomogram finally and validated with concordance index (C-index), calibration plots, Hosmer-Lemeshow test, and internal validation population. Results There were 287 deaths in the training group, which included 6,042 middle-aged and elderly overweight and obese participants in all; and 113 deaths in the verification group, which included 2,590 cases. A total of 9 indicators were included in the modeling group, including gender, age, marriage, hypertension, diabetes, stroke, ADL, IADL, and balance ability to establish a prediction model. The nomogram predicted death with a validated concordance index of (C-index=0.77, 95%CI: 0.74-0.80). The inclusion of balance ability variables in the nomogram maintained predictive accuracy (C-index=0.77, 95%CI:0.73-0.82). The calibration curve graph and Hosmer-Lemeshow test (P > 0.05 for both the modeling group and the verification group) showed the model has a good model consistency. Conclusions In the present study, the death prediction model for overweight and obese middle-aged and elderly people was successfully constructed. In most cases, balance ability is more reversible than other predictors.